(untitled) (Frontiers in Law, 2024)
Artificial intelligence (AI), machine learning (ML) and deep learning (DL) have had a profound impact on various sectors including Banking (Fin Tech), Health (HealthTech) and Charitable Fundraising (Charity Tech). The ‘natural’ ability of an AI system to independently perform and, often, outthink its human-counter parts by developing ‘intelligence’(simulating human intelligence) through its own experiences and processing deep layers of information i.e., complex representations of data, and learn has resulted in astounding improvements in the completion of tasks that are complex and technical, time-consuming.AI, with the ease of working with the most granular level of detail, can identify people and objects, recognise voices, uncover patterns and, in advance, screen for problems. Yet, RegTech (or LawTech/LegalTech) has not seen the same level of advancement. AI can provide solutions and enormous economic, political, and social benefits – in terms of public service administration. The purpose of this article is to explore advents in AI (ML and DL) and whether the criminal justice system, in the United Kingdom (UK), which is heavily overburdened, could benefit from some of the advances that have taken place in other sectors and jurisdictions, and whether automation and algorithmic decision making could be used to modernise it. This research draws on domestic and international published law, regulation, and literature, and isset out in six parts, the first partre views the position of the criminal justice system i.e., issues, part two then looks at relative technological advancements in AI, and the Metaverse. Part three explores current advents in AI relating to RegTech (LawTech/LegalTech) and how, if at all, the CJS can use this technology. Part four explores what aspects of the U.K.’s CJS would be fit for automation. Part five focuses on those matters pertaining to AI that pose problems in relation to matters in part 4 i.e., AI discrimination and bias, and explores safeguarding and mitigation including the requirement for explanation as set out in the GDPR. Part six concludes the discussion with some recommendations, as at, January 2024. It is suggested that AI and algorithmic decision making, with the correct legal framework and safeguards in place, could assist in modernising the CJS focussed legal functions, services in law firms, innovating for the next decade. This work is original and timely given the increased debate relating to how AI can assist in modernising the U.K.’s CJS, the global criminal justice challenges, solutions, and what, if any, role the Metaverse can play.